Voter’s party congruence of Democratic Rally: The change in proximity between the party and its voters - Ioannidis, Nikandros (My University, 2019)
From the day of its establishment, the Democratic Rally was the party which unified the Right in Cyprus. The circumstances under which he was created by Glafcos Clerides affected the character of the party, which at that time (1976) was the main advocate of the Cypriot nationalist faction. However, in recent years the party has transformed, taking a pro-reconciliation, progressive position (Sandal & Loizides, 2013). The present study examines whether there is still any significant difference between DISY and its voters regarding the solution of the Cyprus Problem. It examines, through the use of quantitative data taken from Choose4Cyprus (the only VAA in the island), the political course of DISY and its voters in the political space and the congruence also between DISY and its voters, from 2011 to 2016. Through statistical analysis of the data, the results that emerged denied the case of a separation line between DISY and its voters on the Cyprus Problem. The congruence of the party with its voters increased through the years. Also, 2013 was proved to be a dramatic time period for the political scene of Cyprus.
Keywords: Congruence; Cyprus; Democratic Rally